Some Remarks on the Complex Stability Radius of Differential-Algebraic Equations - Hoang, Le Huy (VNU Journal of Science: Mathematics - Physics, 2013)
Abstract. This paper is concerned with the robust stability of linear differential-algebraic equations (DAEs). A system of linear DAEs subjected to structured perturbation is considered. Computable formulas of the complex stability radius are given and analysed. A comparison of our formula to previous results is given. Keywords: linear differential-algebraic equations, index of matrix pencil, asymptotic stability, structured perturbation, complex stability radius.